Proteomics and transcriptomics analyses of Arabidopsis floral buds uncover important functions of ARABIDOPSIS SKP1-LIKE1. Issue 1 (December 2016) - Lu, Dihong; Ni, Weimin; Stanley, Bruce; Ma, Hong
Abstract Background The ARABIDOPSIS SKP1-LIKE1 (ASK1) protein functions as a subunit of SKP1-CUL1-F-box (SCF) E3 ubiquitin ligases. Previous genetic studies showed that ASK1 plays important roles in Arabidopsis flower development and male meiosis. However, the molecular impact of ASK1-containing SCF E3 ubiquitin ligases (ASK1-E3s) on the floral proteome and transcriptome is unknown. Results Here we identified proteins that are potentially regulated by ASK1-E3s by comparing floral bud proteomes of wild-type and theask1 mutant plants. More than 200 proteins were detected in theask1 mutant but not in wild-type and >300 were detected at higher levels in theask1 mutant than in wild-type, but their RNA levels were not significantly different between wild-type andask1 floral buds as shown by transcriptomics analysis, suggesting that they are likely regulated at the protein level by ASK1-E3s. Integrated analyses of floral proteomics and transcriptomics ofask1 and wild-type uncovered several potential aspects of ASK1-E3 functions, including regulation of transcription regulators, kinases, peptidases, and ribosomal proteins, with implications on possible mechanisms of ASK1-E3 functions in floral development. Conclusions Our results suggested that ASK1-E3s play important roles in Arabidopsis protein degradation during flower development. This study opens up new possibilities for further functional studies of these candidate E3 substrates.